Common plantain. A collection of expressed sequence tags from vascular tissue and a simple and efficient transformation method. - Pommerrenig, Benjamin; Barth, Inga; Niedermeier, Matthias; Kopp, Sina; Klebl, Franz; Sauer, Norbert; et al. (Plant Physiology, 2006)
The vascular tissue of higher plants consists of specialized cells that differ from all other cells with respect to their shape and size, their organellar composition, their extracellular matrix, the type of their plasmodesmata, and their physiological functions. Intact and pure vascular tissue can be isolated easily and rapidly from leaf blades of common plantain (Plantago major), a plant that has been used repeatedly for molecular studies of phloem transport. Here, we present a transcriptome analysis based on 5,900 expressed sequence tags (ESTs) and 3,247 independent mRNAs from the Plantago vasculature. The vascular specificity of these ESTs was confirmed by the identification of well-known phloem or xylem marker genes. Moreover, reverse transcription-polymerase chain reaction, macroarray, and northern analyses revealed genes and metabolic pathways that had previously not been described to be vascular specific. Moreover, common plantain transformation was established and used to confirm the vascular specificity of a Plantago promoter-beta-glucuronidase construct in transgenic Plantago plants. Eventually, the applicability and usefulness of the obtained data were also demonstrated for other plant species. Reporter gene constructs generated with promoters from Arabidopsis (Arabidopsis thaliana) homologs of newly identified Plantago vascular ESTs revealed vascular specificity of these genes in Arabidopsis as well. The presented vascular ESTs and the newly developed transformation system represent an important tool for future studies of functional genomics in the common plantain vasculature.

Differential regulation of sorbitol and sucrose loading into the phloem of Plantago major in response to salt stress. - Pommerrenig, Benjamin; Stal Papini, Flavia; Sauer, Norbert (Plant Physiology, 2007)
Several plant families generate polyols, the reduced form of monosaccharides, as one of their primary photosynthetic products. Together with sucrose (Suc) or raffinose, these polyols are used for long-distance allocation of photosynthetically fixed carbon in the phloem. Many species from these families accumulate these polyols under salt or drought stress, and the underlying regulation of polyol biosynthetic or oxidizing enzymes has been studied in detail. Here, we present results on the differential regulation of genes that encode transport proteins involved in phloem loading with sorbitol and Suc under salt stress. In the Suc- and sorbitol-translocating species Plantago major, the mRNA levels of the vascular sorbitol transporters PmPLT1 and PmPLT2 are rapidly up-regulated in response to salt treatment. In contrast, mRNA levels for the phloem Suc transporter PmSUC2 stay constant during the initial phase of salt treatment and are down-regulated after 24 h of salt stress. This adaptation in phloem loading is paralleled by a down-regulation of mRNA levels for a predicted sorbitol dehydrogenase (PmSDH1) in the entire leaf and of mRNA levels for a predicted Suc phosphate synthase (PmSPS1) in the vasculature. Analyses of Suc and sorbitol concentrations in leaves, in enriched vascular tissue, and in phloem exudates of detached leaves revealed an accumulation of sorbitol and, to a lesser extent, of Suc within the leaves of salt-stressed plants, a reduced rate of phloem sap exudation after NaCl treatment, and an increased sorbitol-to-Suc ratio within the phloem sap. Thus, the up-regulation of PmPLT1 and PmPLT2 expression upon salt stress results in a preferred loading of sorbitol into the phloem of P. major.

Functional characterisation and cell specificity of BvSUT1, the transporter that loads sucrose into the phloem of sugar beet (Beta vulgaris L.) source leaves. - Nieberl, Petra; Ehrl, Christine; Pommerrenig, Benjamin; Graus, D.; Marten, I.; Jung, B.; Ludewig, F.; Koch, W.; Harms, K.; Flügge, U. I.; Neuhaus, H. E.; Hedrich, R.; et al. (Plant Biology, 2017)
Sugar beet (Beta vulgaris L.) is one of the most important sugar-producing plants worldwide and provides about one third of the sugar consumed by humans. Here we report on molecular characterisation of the BvSUT1 gene and on the functional characterisation of the encoded transporter. In contrast to the recently identified tonoplast-localised sucrose transporter BvTST2.1 from sugar beet taproots, which evolved within the monosaccharide transporter (MST) superfamily, BvSUT1 represents a classical sucrose transporter and is a typical member of the disaccharide transporter (DST) superfamily. Transgenic Arabidopsis plants expressing the β-GLUCURONIDASE (GUS) reporter gene under control of the BvSUT1-promoter showed GUS histochemical staining of their phloem; an anti-BvSUT1-antiserum identified the BvSUT1 transporter specifically in phloem companion cells. After expression of BvSUT1 cDNA in bakers' yeasts (Saccharomyces cerevisiae) uptake characteristics of the BvSUT1 protein were studied. Moreover, the sugar beet transporter was characterised as a proton-coupled sucrose symporter in Xenopus laevis oocytes. Our findings indicate that BvSUT1 is the sucrose transporter that is responsible for loading of sucrose into the phloem of sugar beet source leaves delivering sucrose to the storage tissue in sugar beet taproot sinks.

Identification of the transporter responsible for sucrose accumulation in sugar beet taproots. - Jung, Benjamin; Ludewig, Frank; Schulz, Alexander; Meißner, Garvin; Wöstefeld, Nicole; Flügge, Ulf-Ingo; Pommerrenig, Benjamin; Wirsching, Petra; Sauer, Norbert; Koch, Wolfgang; Sommer, Frederik; Mühlhaus, Timo; et al. (Nature Plants, 2015)
Sugar beet provides around one third of the sugar consumed worldwide and serves as a significant source of bioenergy in the form of ethanol. Sucrose accounts for up to 18% of plant fresh weight in sugar beet. Most of the sucrose is concentrated in the taproot, where it accumulates in the vacuoles. Despite 30 years of intensive research, the transporter that facilitates taproot sucrose accumulation has escaped identification. Here, we combine proteomic analyses of the taproot vacuolar membrane, the tonoplast, with electrophysiological analyses to show that the transporter BvTST2.1 is responsible for vacuolar sucrose uptake in sugar beet taproots. We show that BvTST2.1 is a sucrose-specific transporter, and present evidence to suggest that it operates as a proton antiporter, coupling the import of sucrose into the vacuole to the export of protons. BvTST2.1 exhibits a high amino acid sequence similarity to members of the tonoplast monosaccharide transporter family in Arabidopsis, prompting us to rename this group of proteins 'tonoplast sugar transporters'. The identification of BvTST2.1 could help to increase sugar yields from sugar beet and other sugar-storing plants in future breeding programs.

Isolation of AtSUC2 promoter-GFP-marked companion cells for patch-clamp studies and expression profiling - Pommerrenig, Benjamin; Sauer, Norbert; et al. (Plant Journal, 2003)
K channels control K homeostasis and the membrane potential in the sieve element/companion cell complexes. K channels from Arabidopsis phloem cells expressing green fluorescent protein (GFP) under the control of the AtSUC2 promoter were analysed using the patch-clamp technique and quantitative RT-PCR. Single green fluorescent protoplasts were selected after being isolated enzymatically from vascular strands of rosette leaves. Companion cell protoplasts, which could be recognized by their nucleus, vacuole and chloroplasts, and by their expression of the phloem-specific marker genes SUC2 and AHA3, formed the basis for a cell-specific cDNA library and expressed sequence tag (EST) collection. Although we used primers for all members of the Shaker K channel family, we identified only AKT2, KAT1 and KCO6 transcripts. In addition, we also detected transcripts for AtPP2CA, a protein phosphatase, that interacts with AKT2/3. In line with the presence of the K channel transcripts, patch-clamp experiments identified distinct K channel types. Time-dependent inward rectifying K currents were activated upon hyperpolarization and were characterized by a pronounced Ca-sensitivity and inhibition by protons. Whole-cell inward currents were carried by single K -selective channels with a unitary conductance of approximately 4 pS. Outward rectifying K channels (approximately 19 pS), with sigmoidal activation kinetics, were elicited upon depolarization. These two dominant phloem K channel types provide a versatile mechanism to mediate K fluxes required for phloem action and potassium cycling.
Keywords: Arabidopsis thaliana; Companion cells; EST library; Laser microdissection; Phloem; Potassium channels

Phloem-specific expression of Yang cycle genes and identification of novel Yang cycle enzymes in Plantago and Arabidopsis. - Pommerrenig, Benjamin; Feussner, Kirstin; Zierer, Wolfgang; Rabinovych, Valentyna; Klebl, Franz; Feussner, Ivo; Sauer, Norbert (The Plant Cell, 2011)
The 5-methylthioadenosine (MTA) or Yang cycle is a set of reactions that recycle MTA to Met. In plants, MTA is a byproduct of polyamine, ethylene, and nicotianamine biosynthesis. Vascular transcriptome analyses revealed phloem-specific expression of the Yang cycle gene 5-METHYLTHIORIBOSE KINASE1 (MTK1) in Plantago major and Arabidopsis thaliana. As Arabidopsis has only a single MTK gene, we hypothesized that the expression of other Yang cycle genes might also be vascular specific. Reporter gene studies and quantitative analyses of mRNA levels for all Yang cycle genes confirmed this hypothesis for Arabidopsis and Plantago. This includes the Yang cycle genes 5-METHYLTHIORIBOSE-1-PHOSPHATE ISOMERASE1 and DEHYDRATASE-ENOLASE-PHOSPHATASE-COMPLEX1. We show that these two enzymes are sufficient for the conversion of methylthioribose-1-phosphate to 1,2-dihydroxy-3-keto-5-methylthiopentene. In bacteria, fungi, and animals, the same conversion is catalyzed in three to four separate enzymatic steps. Furthermore, comparative analyses of vascular and nonvascular metabolites identified Met, S-adenosyl Met, and MTA preferentially or almost exclusively in the vascular tissue. Our data represent a comprehensive characterization of the Yang cycle in higher plants and demonstrate that the Yang cycle works primarily in the vasculature. Finally, expression analyses of polyamine biosynthetic genes suggest that the Yang cycle in leaves recycles MTA derived primarily from polyamine biosynthesis.

Phloem-Specific Methionine Recycling Fuels Polyamine Biosynthesis in a Sulfur-Dependent Manner and Promotes Flower and Seed Development. - Zierer, Wolfgang; Hajirezaei, Mohammad R.; Eggert, Kai; Sauer, Norbert; von Wirén, Nicolaus; Pommerrenig, Benjamin (Plant Physiology, 2016)
The Yang or Met Cycle is a series of reactions catalyzing the recycling of the sulfur (S) compound 5'-methylthioadenosine (MTA) to Met. MTA is produced as a by-product in ethylene, nicotianamine, and polyamine biosynthesis. Whether the Met Cycle preferentially fuels one of these pathways in a S-dependent manner remained unclear so far. We analyzed Arabidopsis (Arabidopsis thaliana) mutants with defects in the Met Cycle enzymes 5-METHYLTHIORIBOSE-1-PHOSPHATE-ISOMERASE1 (MTI1) and DEHYDRATASE-ENOLASE-PHOSPHATASE-COMPLEX1 (DEP1) under different S conditions and assayed the contribution of the Met Cycle to the regeneration of S for these pathways. Neither mti1 nor dep1 mutants could recycle MTA but showed S-dependent reproductive failure, which was accompanied by reduced levels of the polyamines putrescine, spermidine, and spermine in mutant inflorescences. Complementation experiments with external application of these three polyamines showed that only the triamine spermine could specifically rescue the S-dependent reproductive defects of the mutant plants. Furthermore, expressing gene-reporter fusions in Arabidopsis showed that MTI1 and DEP1 were mainly expressed in the vasculature of all plant parts. Phloem-specific reconstitution of Met Cycle activity in mti1 and dep1 mutant plants was sufficient to rescue their S-dependent mutant phenotypes. We conclude from these analyses that phloem-specific S recycling during periods of S starvation is essential for the biosynthesis of polyamines required for flowering and seed development.

SUCROSE TRANSPORTER 5 supplies Arabidopsis embryos with biotin and affects triacylglycerol accumulation - Pommerrenig, Benjamin; Popko, Jennifer; Heilmann, Martin; Schulmeister, Sylwia; Dietel, Katharina; Schmitt, Bianca; Stadler, Ruth; Feussner, Ivo; Sauer, Norbert (Plant Journal, 2013)
The Arabidopsis SUC5 protein represents a classical sucrose/H(+) symporter. Functional analyses previously revealed that SUC5 also transports biotin, an essential co-factor for fatty acid synthesis. However, evidence for a dual role in transport of the structurally unrelated compounds sucrose and biotin in plants was lacking. Here we show that SUC5 localizes to the plasma membrane, and that the SUC5 gene is expressed in developing embryos, confirming the role of the SUC5 protein as substrate carrier across apoplastic barriers in seeds. We show that transport of biotin but not of sucrose across these barriers is impaired in suc5 mutant embryos. In addition, we show that SUC5 is essential for the delivery of biotin into the embryo of biotin biosynthesis-defective mutants (bio1 and bio2). We compared embryo and seedling development as well as triacylglycerol accumulation and fatty acid composition in seeds of single mutants (suc5, bio1 or bio2), double mutants (suc5 bio1 and suc5 bio2) and wild-type plants. Although suc5 mutants were like the wild-type, bio1 and bio2 mutants showed developmental defects and reduced triacylglycerol contents. In suc5 bio1 and suc5 bio2 double mutants, developmental defects were severely increased and the triacylglycerol content was reduced to a greater extent in comparison to the single mutants. Supplementation with externally applied biotin helped to reduce symptoms in both single and double mutants, but the efficacy of supplementation was significantly lower in double than in single mutants, showing that transport of biotin into the embryo is lower in the absence of SUC5.